Cochrane meta-analysis: teicoplanin versus vancomycin for proven or suspected infection - Diogo Diniz Gomes Bugano (Einstein (São Paulo), 2011)
Objective: To compare efficacy and safety of vancomycin versusteicoplanin in patients with proven or suspected infection.Methods: Data Sources: Cochrane Renal Group’s SpecializedRegister, CENTRAL, MEDLINE, EMBASE, nephrology textbooksand review articles. Inclusion criteria: Randomized controlled trialsin any language comparing teicoplanin to vancomycin for patientswith proven or suspected infection. Data extraction: Two authorsindependently evaluated methodological quality and extracted data.Study investigators were contacted for unpublished information. Arandom effect model was used to estimate the pooled risk ratio (RR)with 95% confidence interval (CI). Results: A total of 24 studies (2,610patients) were included. The drugs had similar rates of clinical cure(RR: 1.03; 95%CI: 0.98-1.08), microbiological cure (RR: 0.98; 95%CI:0.93-1.03) and mortality (RR: 1.02; 95%CI: 0.79-1.30). Teicoplaninhad lower rates of skin rash (RR: 0.57; 95%CI: 0.35-0.92), red mansyndrome (RR: 0.21; 95%CI: 0.08-0.59) and total adverse events (RR:0.73; 95%CI: 0.53-1.00). Teicoplanin reduced the risk of nephrotoxicity(RR: 0.66; 95%CI: 0.48-0.90). This effect was consistent for patientsreceiving aminoglycosides (RR: 0.51; 95%CI: 0.30-0.88) or havingvancomycin doses corrected by serum levels (RR: 0.22; 95%CI:0.10-0.52). There were no cases of acute kidney injury needingdialysis. Limitations: Studies lacked a standardized definition fornephrotoxicity. Conclusions: Teicoplanin and vancomycin are equallyeffective; however the incidence of nephrotoxicity and other adverseevents was lower with teicoplanin. It may be reasonable to considerteicoplanin for patients at higher risk for acute kidney injury.